Review article: emulsifiers in the food supply and implications for gastrointestinal disease. Issue 1 (28th November 2018) - Halmos, Emma P.; Mack, Alexandra; Gibson, Peter R.
Summary: Background: Dietary emulsifiers are the latest food additives to be associated with intestinal, cardiovascular and metabolic health. Most recently, there are postulations around certain emulsifiers playing a role in the development of Crohn's disease. Aim: To review the use of food‐based emulsifiers, their content in the food supply and mechanisms by which they might exert potentially detrimental biological effects. Methods: Information on emulsifiers and thickeners relevant to human health was critically examined. Results: The term, "emulsifier, " has been used loosely and has included thickeners as well as agents that truly promote emulsions. These comprise proteins, phospholipids and carbohydrates, alone or in combination, and play roles in optimising food appearance, texture and mouthfeel, delivering or disguising flavours and achieving palatable low‐fat foods. Their presence in the food supply is common, but not "ubiquitous" as frequently stated. Strict regulations limit the amount added to foods, but the lack of established methodologies to measure the actual food content of these diverse compounds limits our knowledge of consumption. Emulsifiers and thickeners have effects on the gut microbiota, mucosal barrier and inflammatory pathways, and can induce disease in experimental models. However, differentiating pharmacological from physiological effects and translating findings in experimental animals to humans raise uncertainties about the relevance of such effects. Conclusions: There is limited evidence to directly link emulsifiers and thickeners to human disease, but multiple potential pathogenic mechanisms. Knowledge of actual dietary intake and high‐quality interventional studies is needed to enable the risks associated with their intake to be understood.